The Dynamic Relationship between Energy Consumption and Level of Unemployment Rates in Malaysia: A Time Series Analysis Based on ARDL Estimation - Borhan, Halimahton; Ridzuan, Abdul Rahim; Razak, Mohamad Idham Md; Mohamed, Rozita Naina (International Journal of Energy Economics and Policy, 2023)
Unemployment rates is a social economic problem that needs further attention in most country in the world including Malaysia as it affects the citizen’s wellbeing. The studies on the macroeconomic determinants such as energy consumption for unemployment rates is hardly find in the previous studies. Higher energy consumption will usually lead to lower unemployment rates because people need to find a job and pay their bills. In these papers, we aim to investigates more macroeconomic variables impacts such as foreign investment, domestic investment, trade liberalization, inflation, urbanization, economic growth, corruption, besides energy consumption on level of unemployment rates for Malaysia. The paper utilized ARDL estimation based on annul data starting from 1984 until 2020. The outcomes revelas a mix expected sign between the independent variable and the dependent variables for the long run. Based on energy consumption, it is found that is also negatively influences the level of unemployment rates in the short run but not in the long run. The list of possible policy recommendation is highlighted at the end of this paper.